Scanning life's matrix genes, proteins, and small molecules - Stuart L. Schreiber, lecturer; Eric S. Lander, lecturer; Ann DeStefano Sutherland, producer; Wally Ashby, director; Howard Hughes Medical Institute (Chevy Chase, MD Howard Hughes Medical Institute, 2003)
Four lectures on genomic science and chemical genetics, with emphasis on how molecular biology, robotics, and advanced computation are combining to characterize a new generation of biomedical research.
Reading genes and genomes / Eric S. Lander (60 min.) -- Probing genes and genomes / Stuart L. Schreiber (60 min.) -- Human genomics : a new guide for medicine / Eric S. Lander (60 min.) -- Chemical genomics : new tools for medicine / Stuart L. Schreiber (60 min.)
Howard Hughes Medical Institute holiday lectures on science, December 2002.
Keywords: Human genome; Human molecular genetics; Biochemical genetics; Medical genetics; Genomics; Molecular Biology